Religion and media: a case study ofUtusan Malaysia's response to HIV/AIDS - Tham, J.S.; Zanuddin, H. (Taylor & Francis, 2015)
As a Muslim country, Malaysia is no longer coy about the claim that its communities are protected from HIV/AIDS infection due to their religious and cultural norms. On the reverse, more than 70% of people living with HIV/AIDS are Muslims in the current setting. Despite the Islamic tenets prohibiting extramarital and premarital sex, as well as illicit drug and alcohol intake, some Muslims do still engage in such high-risk activities that could lead to HIV infection. While it is plausible that media could be a platform for change in terms of fostering positive behavioural change to curtail the relentless pace of the epidemic, research on the role of media in advocating positive behavioural change and prevention against HIV/AIDS through Islam's point of view remains largely unexplored. The purpose of this paper is, therefore, to explore how the Islamic tenets and beliefs are being instilled in the Utusan Malaysia for halting the spread of HIV/AIDS among the Muslims. The results show that overall only six articles related to HIV/AIDS review the epidemic from an Islamic point of view and published in the daily. In spite of the photographs picturing thousands of words, only two news photographs captured the imagination and gained the respect of the religion on the issue of HIV/AIDS.